Fejlettségi mutatók értékelésének változása Európában egy adatbázis alapján = Changing evaluation of development indicators in Europe in the case of a specific database - Szabó, Pál (Közép-Európai Közlemények, 2017)
This article examines a special collection of European development indicators, which was published in a university book in the 90’s. The results show that somé of the indicators are useable nowadays alsó, bút somé of them are outdated, and the evaluation of somé indicators have changed. The obsolescence is connected to the life cycle of products or to the quick development. The reason of the changing evaluation is the changing point of view: in this century in Europe the society and the environment has got more attention, and the priority of the economy and economic development has weakened. If we analyze the data, the results show that in our continent the gap between West and East is weakened. In the second part of this paper we made a new selection of development indicators fór European countries, considering the complexity of areas and the new important elements, attributions of the society, economy and environment. State of development is a fundamental idea in régiónál policy and considerable amount of money is attached to it (financial aid fór the poor countries, support fór the convergence regions in the EU). Fór this reason, the measurement of the development is essential demand.